Guarani Virophage, a New Sputnik-Like Isolate From a Brazilian Lake - Mougari, Said; Bekliz, Meriem; Abrahao, Jonatas; Di Pinto, Fabrizio; Levasseur, Anthony; La Scola, Bernard (Frontiers in Microbiology, 2019)
Virophages are critical regulators of viral population dynamics and potential actors in the stability of the microbial networks. These small biological entities predate the replicative cycle of giant viruses, such as the members of the Mimiviridae family or their distant relatives, which produce within the cytoplasm of their host cells a viral factory harboring a complex biochemistry propitious to the growth of the smaller parasites. In this paper, we describe the isolation and the characterization of a new virophage, the eighth, that we named Guarani. We observed that Guarani exhibits a late replication cycle compared to its giant virus host. In addition, like all Sputnik, Guarani is able to infect the three lineages A, B and C of the Mimiviridae family, and affects the replication and the infectivity of its host virus. In terms of genetic content, Guarani has a 18,967 bp long double-stranded DNA genome encoding 22 predicted genes very similar to Sputnik genes, except for ORF19 and ORF12. The former is more related to Zamilon while the latter seems to be novel. The architecture of the Guarani genome is closely related to Sputnik and Zamilon strains, suggesting a common origin for all these virophages.